El rol del maestro frente a la construcción del juego simbólico en los niños (2009)
In this article are presented 3 situations of spontaneous activities developed by preschool children and first grade of elementary children, whose analysis is orienting a reference frame. It seeks to show comprehensive elements to teachers, in order that they can have them at their disposal to offer children possibilities which let them to transform of their stereotyped experiences of games, called toys- games into symbolic games. The observation and the analysis of the activities performed by children, shows how they organize new representations from the new meanings that they give to their experiences. Faced to these children's processes, the teacher has a basic role to offer the meaningful experiences that support the learning processes.